Мікроморфологічні особливості насінини видів роду Begonia L. (Begoniaceae Putz.) - Belaeva, Ya.V. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2012)
In this paper seed characteristics of 12 Begonia species belonging to 6 sections were studied with SEM in order to define the diversity seed coat cells shape. Seeds of 9 studied species, which belong to 4 sections of Begonia, showed micromorphological features which are typical for aerochorous Begonia species, while B. dregeі showed micromorphological features which are typical for hydrochorus species. It has been revealed that the differences in seed characteristics help to separate the Begonia at species level.